Analysis of N-glycosylation in maize cytokinin oxidase/dehydrogenase 1 using a manual microgradient chromatographic separation coupled offline to MALDI-TOF/TOF mass spectrometry - Franc, Vojtěch; Sebela, Marek; Rehulka, Pavel; Končitíková, Radka; Lenobel, René; Madzak, Catherine; Kopečný, David (Journal of proteomics, 2012)
Cytokinin oxidase/dehydrogenase (CKO; EC 1.5.99.12) irreversibly degrades the plant hormones cytokinins. A recombinant maize isoenzyme 1 (ZmCKO1) produced in the yeast Yarrowia lipolytica was subjected to enzymatic deglycosylation by endoglycosidase H. Spectrophotometric assays showed that both activity and thermostability of the enzyme decreased after the treatment at non-denaturing conditions indicating the biological importance of ZmCKO1 glycosylation. The released N-glycans were purified with graphitized carbon sorbent and analyzed by MALDI-TOF MS. The structure of the measured high-mannose type N-glycans was confirmed by tandem mass spectrometry (MS/MS) on a Q-TOF instrument with electrospray ionization. Further experiments were focused on direct analysis of sugar binding. Peptides and glycopeptides purified from tryptic digests of recombinant ZmCKO1 were separated by reversed-phase chromatography using a manual microgradient device; the latter were then subjected to offline-coupled analysis on a MALDI-TOF/TOF instrument. Glycopeptide sequencing by MALDI-TOF/TOF MS/MS demonstrated N-glycosylation at Asn52, 63, 134, 294, 323 and 338. The bound glycans contained 3-14 mannose residues. Interestingly, Asn134 was found only partially glycosylated. Asn338 was the sole site to carry large glycan chains exceeding 25 mannose residues. This observation demonstrates that contrary to a previous belief, the heterologous expression in Y. lipolytica may lead to locally hyperglycosylated proteins.
Keywords: Zea mays; Tandem Mass Spectrometry; Molecular Sequence Data; klonování DNA; molekulární sekvence - údaje; kukuřice setá; Recombinant Proteins; Yarrowia; tandemová hmotnostní spektrometrie; oxidoreduktasy; Amino Acid Sequence; rekombinantní proteiny; glykosylace; spektrometrie hmotnostní - ionizace laserem za účasti matrice; Enzyme Stability; Polysaccharides; polysacharidy; Cloning, Molecular; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; Glycosylation; Oxidoreductases; stabilita enzymů; sekvence aminokyselin